Amizades interculturais : um estudo com gregos no Espírito Santo - Costa, Lorena Queiroz Merizio (2012)
International migration brings important changes to the lives of human beings, including their friendships. The friendship between people of different nationalities can bring information about the cultural characteristics and modes of relationship peculiar to different people. Therefore, the objective of this research was to describe the friendships in the story of Greek immigrants living in the Espírito Santo state, with other Greeks, Brazilians and other foreigners, in order to understand the relationship between friendship and culture, also including intercultural friendships and role friendships in the process of adapting or adjusting to life in Brazil. The specific objectives were to describe the history of friendships after migrating to Brazil, the content of these friendships, and the role of the same adaptation of the Greeks to Brazil. The participants were ten Greek immigrants who came to Brazil with ten years of age or older, who were interviewed. The results indicated that friendships are part of the history of these immigrants in a new country. The meaning of friendship includes amplitude, freedom, spontaneity, selflessness, honesty, sincerity, loyalty, reliability and longevity. The main dimensions of friendship were similarities and differences, proximity and distance, support, reciprocity and conflict. Relations between friendship and social context or sociocultural environment included receptivity and rejection, adoption and adaptation, connection and disconnection, friendship and community abroad, democracy, family, work and school. The results were discussed in light of the work of Robert Hinde. It was noted that the friendship acts as a mediator of adaptation to the new country from abroad - despite their cultural variations - a condition representing not only active in various traditions, but allowing communication between these customs, contributing to immigrants feel welcomed within the cultural nation that chose to live.